A novel synthesis of N-hydroxy-3-aroylindoles and 3-aroylindoles12. Issue 38 (1st August 2018) - Ieronimo, Gabriella; Palmisano, Giovanni; Maspero, Angelo; Marzorati, Alessandro; Scapinello, Luca; Masciocchi, Norberto; Cravotto, Giancarlo; Barge, Alessandro; Simonetti, Marco; Ameta, Keshav Lalit; Nicholas, Kenneth M.; Penoni, Andrea
Abstract : A straightforward indole synthesis via annulation of C -nitrosoaromatics with conjugated terminal alkynones was realised achieving 3-aroylindoles regioselectively. Abstract : A straightforward indole synthesis via annulation of C -nitrosoaromatics with conjugated terminal alkynones was realised achieving a simple, highly regioselective, atom- and step economical access to 3-aroylindoles in moderate to good yields. Further functionalizations of indole scaffolds were investigated and an easy way to JWH-018, a synthetic cannabinoid, was achieved.